Salt-tolerant α-arabinofuranosidase from a new specie Aspergillus hortai CRM1919: Production in acid conditions, purification, characterization and application on xylan hydrolysis - Terrone, Cárol Cabral [UNESP]; Montesino de Freitas Nascimento, Juliana [UNESP]; Fanchini Terrasan, César Rafael; Brienzo, Michel [UNESP]; Carmona, Eleonora Cano [UNESP] (Elsevier, 2020)
Hemicelluloses are mainly branched heteropolysaccharides composed by xylose, arabinose, mannose, galactose, rhamnose and glucose. The main hemicellulose is xylan, a structure composed by xylose main chain branched with other monosaccharides or glucuronic and galacturonic acids. Among various hydrolytic enzymes acting on the degradation of xylan, α-L-arabinofuranosidases catalyze the hydrolysis of linkages between α-L-arabinofuranosides and the polysaccharide main chain. In this study, Aspergillus hortai strain CRM1919, isolated from soil surrounding saline and alkaline lagoons of the Nhecolândia region in Pantanal Matogrossense was investigated regarding the production of α-L-arabinofuranosidases. A. hortai produced α-L-arabinofuranosidase at high levels when cultivated in medium containing citrus pulp and orange peel at 1% (w/v) under static submerged cultures for 4 days and at pH 2.5 and 30 °C. The optimization steps increased 15-fold the enzymatic activity. The purified α-L-arabinofuranosidase was optimally active at pH of 4.0 and 60 °C, presenting half-lives of 265 and 230 min at 30 and 40 °C, respectively. High enzyme stability was observed after 24 h incubation at pH 5.0 and in presence of high concentration of NaCl in the reaction medium. The purified enzyme was mainly active against ρ-nitrophenyl-α-L-arabinofuranoside presenting the following kinetic parameters Km of 8.73 mmol/L, Vmax of 7.91 μmol/min.mg of protein and Kcat of 0.59/min. Hydrolysis of oat xylan performed in the presence of the purified α-arabinofuranosidase individually and in association with a purified xylanase made possible to verify the cooperation between these xylanolytic enzymes and the sequential action of each enzyme in the xylan structure hydrolysis.
Keywords: Accessory enzymes; Citrus pulp; Enzymes cooperation; Glycoside hydrolases; xylan‐degrading enzymes; α-L-arabinofuranosidase